Medical Rehabilitation of Children With Idiopathic Scoliosis: Monotherapy or Combined Therapy. A Systematic Literature Review - Nora Kasparaitytė; Juozas Raistenskis; Lina Budrienė; Tomas Aukštikalnis (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Idiopathic scoliosis is among the most common spinal disorders diagnosed in 1–3% of children and adolescents. Treatment choice is related to disease severity, with a Cobb angle of 20–40°, a corrective brace or physiotherapy can stop its progression. However, insufficient research has shown whether combined treatment is better than monotherapy.